STRATEGI BERTAHAN HIDUP MASYARAKAT DI PINGGIRAN SUNGAI SIAK KELURAHAN TANJUNG RHU KOTA PEKANBARU - Sepriandi "; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Humans and the environment is essentially a building that should be mutually reinforcing because humans are extremely dependent on its environment while the environment also depends on the activity and human activity. But seen from the human side, the environment is something that is passive, while humans are active, so that environmental quality is very dependent on human qualities.Coastal pollution is one form of ecological crisis and one form of damage to the water resources of the river and the sea caused by the removal of industrial waste and household waste into the river. The relationship between the city with the waterfront area has existed since the beginning of human civilization. Where in the past the development of civilization city water body is the only one of the most efficient transport infrastructure, so that the transportation factor into a key contributing factor to the development of a city.This research was conducted in RW 07 is housed in the village of Tanjung Rhu, District Fifty Pekanbaru. The purpose of this study was to determine the socio-economic and cultural conditions of communities on the outskirts of the Siak River in the village of Tanjung Rhu RW 07 Fifty District of Pekanbaru city, as well as To To know how to survive on the fringes of society in RW 07 Siak River Village Tanjung Rhu District of Fifty Cities Pekanbaru.This research is a qualitative descriptive study, the subjects in this study were residents of RW 07 which is housed in the village of Tanjung Rhu, District Fifty Pekanbaru many as eight families. The sampling technique research is purposive sampling technique, which the researchers have determined the subject of research based on the characteristics desired by the researchers according to the issues to be investigated. The number of study subjects were determined based on the following criteria : Location Research is a densely populated area, including flood and disaster-prone domiciled research subjects above 10 years.Based on the survey results revealed that the adaptation of rural communities in the Siak river study sites, namely the more often people Village Tanjung Rhu RW 07, District of Pekanbaru City Fifty adaptation action, more action adjustment is made public with the environment in order to survive. Most of livelihood as day laborers and the income earned is uncertain. Solidarity between them and their preconceived very protecting and maintaining the solidarity among them.Keywords: Survival Strategies, Adaptation, Community, Fringe Siak River.